2013
DOI: 10.1111/jphp.12146
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution and pharmacokinetics of baicalin–polyvinylpyrrolidone coprecipitate

Abstract: From these observations of improved dissolution and pharmacokinetic behaviours, a good relationship was found in vitro and in vivo, indicating that the coprecipitate could be a promising formulation strategy for insoluble baicalin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…However, the phase behaviour of solid dispersion can be extremely complicated. Drug and polymer may be miscible, partially miscible or immiscible …”
Section: The Role Of Interactions In Drug–polymer Miscibilitymentioning
confidence: 99%
“…However, the phase behaviour of solid dispersion can be extremely complicated. Drug and polymer may be miscible, partially miscible or immiscible …”
Section: The Role Of Interactions In Drug–polymer Miscibilitymentioning
confidence: 99%
“…It has attracted increasing attention from worldwide researchers mainly because of its various therapeutic benefits, such as anti‐inflammatory, antiviral, antioxidant and antitumour activities . However, because of the glycosyl group on the ring, BCL is low hydrophilic and poorly absorbed in the small intestine and colon, only moderately absorbed in the stomach, leading to low bioavailability, while its hydrolysate, baicalein was well‐absorbed in the gastrointestinal tract and then restored to BCL in the body . The oral bioavailability of BCL and baicalein was 2.2% and 27.8% in rats respectively .…”
Section: Introductionmentioning
confidence: 99%
“…These have included microspheres, 11 microcapsules, 12 nanoemulsions, 13 inclusion complexes, 14,15 solid lipid nanoparticles, 16 BA-polyvinylpyrrolidone coprecipitate, and a BA-phospholipid complex. 17,18 Indeed, the studies have shown an increased solubility and improvement of oral bioavailability in the preclinical phase. However, the currently marketed preparations, including BA capsules and tablets, have to be administered at a large dose to obtain effective drug plasma concentration, due to low oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%